Phenological growth stages of Silybum marianum according to the extended BBCH scale. (27th October 2014) - Martinelli, T.; Andrzejewska, J.; Salis, M.; Sulas, L.
Abstract Silybum marianum is a medicinal plant cultivated for silymarin production in central Europe and Asia. It is also considered a weed of both arable lands and pastures. Although S. marianum still exhibits traits that are typical of wild species; both its fruit and biomass productivity are remarkable. Therefore, the species is gaining interest as a potential novel commercial crop for multiple uses (i.e. medicinal plant, bioenergy, and vegetable oil production). Despite the intriguing characteristics of this plant and its economic importance, a detailed description of the phenological growth stages of S. marianum has never been developed. A precise and univocal description of the growth stages of this species will offer a useful tool for several agronomic and research activities, weed management practices and for further genetic improvement programmes. In the present manuscript, the description of the phenological development of S. marianum is proposed utilising the extended BBCH (Biologische Bundesantalt, Bundessortenamt and Chemische Industrie) scale. The phenological growth stages are described utilising both the 2‐ and 3‐digit BBCH coding system. Pictures of the most representative stages supplement the manuscript.